Contribution of the serine protease HtrA in Escherichia coli to infection in foxes. (October 2019) - Zhang, Zhiqiang; Wu, Tonglei; Li, Yonghui; Bai, Xue; Yan, Xijun; Gao, Yunhang; Shi, Qiumei; Zhu, Guoqiang
Abstract: Escherichia coli can cause severe, acute hemorrhagic pneumonia and systemic infection in farmed foxes, raccoon dogs and minks, leading to considerable economic losses to the farmers. It is well established that the htrA -encoded serine protease HtrA is critical for bacterial growth and survival under stress, and HtrA has been determined to be a potential vaccine target. However, the roles of HtrA in E. coli pathogenesis remain unknown. In this study, we generated an htrA -deletion mutant of the E. coli protype strain HBCLE-12 that causes pneumonia in silver foxes and then evaluated the changes in bacterial physiological characteristics in the absence of HtrA. The data show that knockout of the htrA gene did not affect growth and biochemical characteristics but led to impaired virulence of the strain. Increased susceptibility to environmental stresses, impaired survival in serum, and reduced biofilm formation may contribute to the virulence attenuation of the mutant. Furthermore, the HtrA-deficient mutant was subjected to RNA-seq analysis, and 16 differentially expressed genes were determined. This study provided insight that HtrA plays a definitive role in E. coli -induced infection. Highlights: We generated a htra -deletion mutant of E. coli isolate causing pneumonia in foxes. We evaluated the changes of bacterial physiological characteristics without HtrA. The HtrA inactivation leads to attenuated virulence and stress tolerance. Impaired biofilm formation and serum-survival were observed with HtrA knockout. 16 down-regulated genes was determined in HtrA –deficient mutant.